ANALISIS KEKUATAN PEMASANGAN PIPA PVC (PRALON) DALAM KOLOM UNTUK SISTEM DRAINASE MENGGUNAKAN SOFTWARE SPCOLUMN - Raka Maulana Saputra; Bagas Prasetyo; Y Djoko Setiyarto (CRANE: Civil Engineering Research Journal, 2025)
Innovations in modern building design encourage the integration of utility systems, such as rainwater drainage, into structural elements to improve space efficiency and aesthetics. This study aims to analyze the effect of embedding PVC (pralon) pipes as internal drainage channels on the strength and efficiency of reinforced concrete columns. A numerical analysis was carried out using the spColumn software on columns with dimensions of 350 × 600 mm, with variations in the number of 4-inch pipes (zero, one, two, and three). The results show that installing one, two, and three pipes gradually reduced the maximum compressive capacity of the column from 4100 kN to 3930 kN, 3790 kN, and 3650 kN, respectively. Despite this reduction, all column configurations were proven to be safe for sustaining the planned ultimate load of 368.72 kN. Interestingly, the structural–material efficiency of the column increased by up to 4.2% in the three-pipe configuration, as the reduction in concrete volume outweighed the decrease in capacity. It is concluded that the integration of PVC drainage pipes into columns offers a structurally safe, functional, and more material-efficient solution. These findings highlight the potential to reduce the need for external drainage channels, thereby improving spatial efficiency and lowering construction costs. Furthermore, integrating the drainage system into columns allows for cleaner, more minimalist façade designs without conventional piping interruptions, ultimately enhancing the aesthetic value and architectural competitiveness of the building.